Efektivitas Metode Bercerita Terhadap Kemampuan Bahasa Melalui Buku Bergambar Pada Anak Usia 5-6 Tahun - St. Aisyah Syahrani; Usman Afdal; Sitti Nurhidayah Ilyas; Muhammad Akil Musi; Yuliani; Norma Sulistiyani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to evaluate the effectiveness of the storytelling method using picture books in improving the language skills of children aged 5-6 years. The research method used was a pseudo-experiment with a pretest-posttest control group design. The research subjects consisted of 30 children who were divided into two groups, namely the experimental group and the control group. The experimental group was given an intervention in the form of a storytelling method with picture books for 8 weeks, while the control group did not get in-tervention. The results showed that there was a significant increase in children's language skills in the experimental group compared to the control group. This improvement was measured through language proficiency test instruments covering aspects of vocabulary, comprehension, and language expression. Statistical analysis showed a p value <0.05, indicating that the storytelling method with picture books is effective in improving the language skills of children aged 5-6 years. This study implies that the picture book storytelling method can be used as an alternative in the language learning process in early childhood. In addition, this study also suggests that educators and parents should be more active in using picture books as a medium to develop children's language skills.